Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Kinerja Guru di SMA PATRIOT Kota Bekasi - Fuadi, Mohamad Farkhan; Akil, Akil; Ramdhani, Khalid (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze the application of transformational leadership by school principals in improving teacher performance at Patriot High School in Bekasi City. The study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study indicate that the principal applies four main dimensions of transformational leadership, namely ideal influence, inspirational motivation, intellectual stimulation, and individual consideration. The implementation of these dimensions is reflected in the principal's exemplary behavior, consistent vision presentation, teacher empowerment through training, and the creation of a collaborative work environment. The strategies used were proven to enhance teachers' motivation, participation, and professionalism. However, several challenges were encountered in their implementation, including time constraints, low enthusiasm among some teachers toward innovation, and generational communication gaps. These findings emphasize that transformational leadership plays a strategic role in enhancing teacher performance, particularly in urban-suburban secondary school settings.